Occurrence and origin of andalusite in peraluminous felsic igneous rocks - Rapela, Carlos Washington (2005)
Andalusite occurs as an accessory mineral in many types of peraluminous felsic igneous rocks, including rhyolites, aplites, granites, pegmatites, and anatectic migmatites. Some published stability curves for And = Sil and the water-saturated granite solidus permit a small stability field for andalusite in equilibrium with felsic melts. We examine 108 samples of andalusite-bearing felsic rocks from more than 40 localities world-wide. Our purpose is to determine the origin of andalusite, including the T-P-X controls on andalusite formation, using eight textural and chemical criteria: size-compatibility with grain sizes of igneous minerals in the same rock; shape-ranging from euhedral to anhedral, with no simple correlation with origin; state of aggregation-single grains or clusters of grains; association with muscovite-with or without rims of monocrystalline or polycrystalline muscovite; inclusions--rare mineral inclusions and melt inclusions; chemical composition-andalusite with little significant chemical variation, except in iron content (0·08-1·71 wt % FeO); compositional zoning--concentric, sector, patchy, oscillatory zoning cryptically reflect growth conditions; compositions of coexisting phases-biotites with high siderophyllite-eastonite contents (Al iv ≈ 2·68 ± 0·07 atoms per formula unit), muscovites with 0·57-4·01 wt % FeO and 0·02-2·85 wt % TiO2, and apatites with 3· 53 ± 0·18 wt % F. Coexisting muscovite-biotite pairs have a wide range of F contents, and FBt = 1·612F Ms + 0·015. Most coexisting minerals have compositions consistent with equilibration at magmatic conditions. The three principal genetic types of andalusite in felsic igneous rocks are: Type 1 Metamorphic-(a) prograde metamorphic (in thermally metamorphosed peraluminous granites), (b) retrograde metamorphic (inversion from sillimanite of unspecified origin), (c) xenocrystic (derivation from local country rocks), and (d) restitic (derivation from source regions); Type 2 Magmatic-(a) peritectic (water-undersaturated, T↑) associated with leucosomes in migmatites, (b) peritectic (water-undersaturated, T↓), as reaction rims on garnet or cordierite, (c) cotectic (water-undersaturated, T↓) direct crystallization from a silicate melt, and (d) pegmatitic (water-saturated, T↓), associated with aplite-pegmatite contacts or pegmatitic portion alone; Type 3 Metasomatic-(water-saturated, magma-absent), spatially related to structural discontinuities in host, replacement of feldspar and/or biotite, intergrowths with quartz. The great majority of our andalusite samples show one or more textural or chemical criteria suggesting a magmatic origin. Of the many possible controls on the formation of andalusite (excess Al2O 3, water concentration and fluid evolution, high Be-B-Li-P, high F, high Fe-Mn-Ti, and kinetic considerations), the two most important factors appear to be excess Al2O3 and the effect of releasing water (either to strip alkalis from the melt or to reduce alumina solubility in the melt). Of particular importance is the evidence for magmatic andalusite in granites showing no significant depression of the solidus, suggesting that the And = Sil equilibrium must cross the granite solidus rather than lie below it. Magmatic andalusite, however formed, is susceptible to supra- or sub-solidus reaction to produce muscovite. In many cases, textural evidence of this reaction remains, but in other cases muscovite may completely replace andalusite leaving little or no evidence of its former existence.